Does political propaganda matter in mitigating climate change? Insights from the United States of America - Abudu, Hermas; Wesseh, Presley K.; Lin, Boqiang (Journal of management science and engineering (Online), 2023)
Some research on climate change has been the basis of climate change denialism (hereafter, CCD is used to refer to denial, denialism, and deniers). There is formative knowledge about the role of political propaganda in climate policies and resulting outcomes. To contribute to the understanding of political ideology and the extent of CCD, we adopt econometric techniques to study the impact of the United States of America's withdrawal from the Paris Agreement. The results show that ideological political propaganda has psychological and philosophical consequences that impact climate change policies. In addition, we find that the effect of a state's economic growth on climate change is mediated by CCD. In particular, low-income capitalist states have a higher propensity to become CCDs because they are more likely to engage in economic expansion even at the expense of environmental sustainability. Global climate change policies depend on high-income nations and industries' willingness to adopt economic policies to achieve sustainable future development. Thus, this study fills the literature gap on the relationship between political ideology and climate change. The findings show that CCD significantly influences voting patterns and socioeconomic outcomes. It impedes states from achieving net-zero emissions and carbon neutrality and it is used as a political propaganda. Subject to these findings, relevant policy suggestions are offered.